Carcass and Organoleptic Characteristics of Duck Meat as Influenced by Breed and Sex - Omojola, A.B. (International Journal of Poultry Science, 2007)
Carcass and meat quality traits of three breeds of duck which include Rouen, Pekins and Muscovy were investigated. A total of thirty-six matured ducks with twelve ducks from each breed were used for the study in a 3×2 (breed×sex) factorial arrangement in a completely randomized design. The ducks were slaughtered in batches of six, properly bled, defeathered and dressed. The ducks were chilled at 2°C for 24 h immediately after dressing, prior to cutting up into primal cuts. Samples for cooking loss, shear force and taste panel evaluations were taken from the breast portion. The dressing percentage was highest in the Muscovy duck with values of 71.18 and 69.75% for male and female respectively while the least value of 65.28% was obtained from the female Rouen duck. The male Muscovy ducks gave the highest absolute values (p0.05) sex effect in the Rouen breed. The moisture content of duck meat evaluated ranged from 72.69 (female Muscovy) to 76.72% for female Rouen ducks. Apart from the male Pekin duck that gave the highest (p0.05). Shear force values of 2.15 and 2.30 kg/cm3 were obtained from the male and female Rouen ducks respectively while higher values of 2.64 and 3.41 kg/cm3 were given by both male and female Pekin ducks. The highest shear force value (3.91 kg/cm3) was obtained from the female Muscovy duck. In terms of flavour, tenderness and juiciness, the taste panelist has higher preference for meat from the male Rouen duck. The result also revealed that sex and breed had no significant (p>0.05) effect on the texture and overall acceptability of duck meat.